When is a CT scan necessary in children and adolescents with cervical spine injury?. Issue 1 (January 2018) - Smaga, Sharon; Rub, Fariha
Abstract : EVIDENCE‐BASED ANSWER : Imaging of the cervical spine should be obtained if the patient has neurologic signs or symptoms or mechanism of injury suggests cervical spine injury. Plain x‐rays should be done first, with computed tomography (CT) of the cervical spine reserved for cases of diagnostic uncertainty or to confirm abnormal plain films (SOR: B, based on a systematic review of retrospective casecontrol studies and case series, and an individual retrospective case‐control study).